2009
DOI: 10.1136/emj.2008.062943
|View full text |Cite
|
Sign up to set email alerts
|

Driving with a forearm plaster cast: patients' perspective

Abstract: It is recommended that all medical professionals advise their patients that they should not drive while immobilised in an upper limb plaster cast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…2 In Australia, up to 50% of adults immobilised in a plaster cast continue to drive despite medical advice to the contrary. 8 Individualised advice based on evidencebased medicine is needed, but the current evidence available is insufficient. [2][3][4][5]10,11 This study had a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…2 In Australia, up to 50% of adults immobilised in a plaster cast continue to drive despite medical advice to the contrary. 8 Individualised advice based on evidencebased medicine is needed, but the current evidence available is insufficient. [2][3][4][5]10,11 This study had a number of limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The east coast Australian study by Kalamaras et al (2006) found that two-thirds of the male participants who broke their wrist drove in a cast, compared to only one-third of females. The difference in the prevalence of drivers between the Edwards et al (2009) and Kalamaris et al (2006) studies may be due to the relative geographies and the social norms in the two countries with regards to the role of driving. There is little understanding of the motivations people have for driving or not driving while their arm or wrist is in plaster and how far psycho-social factors, such as affect or risk taking, may explain some of the differences.…”
Section: Driving With the Wrist Or Hand In Plastermentioning
confidence: 96%
“…Kalamaris et al (2006) found 50% of Australian patients drove their vehicle after having their arm or wrist placed in a plaster cast. Interestingly in Edwards et al's (2009) study three of the 13 patients who were driving ceased on advice given during the project suggesting that they had not received advice prior to making their return to driving decision. Another patient stopped driving when his insurance company told him he was not insured.…”
Section: Driving With the Wrist Or Hand In Plastermentioning
confidence: 97%
See 1 more Smart Citation
“…Survey studies have demonstrated that the majority of patients who have a driver's license drive whilst wearing cast, regardless of whether the doctor has given them advice or not (1,2). Studies conducted on the doctors found that doctors' knowledge on this issue was very limited and non-standardised (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%